Teacher Mentoring: Experiences from International Teacher Mentors in Kazakhstan - Schulleri, Phillipa (Asian Journal of Education and Training, 2020)
In this paper, a closer look at mentoring in education is presented. The research sample was a team of eleven international teachers who were engaged in mentoring local teachers in a high school for gifted students in Kazakhstan. The purpose of the study was to explore the experiences of international teachers, as they relate their experiences of mentoring local teachers. The author sought the stories of the international mentor teachers and the meaning they placed on these experiences. Answers were sought to questions of how mentors defined mentoring, what they perceived as benefits of mentoring, and how they dealt with mentoring difficulties. Face to face semi-structured interviews were used to collect data from eleven volunteering international teachers. Seven categories of mentoring were found to be: Leading, guiding, modelling advising, and exposition; Supporting, challenging and suggesting, exploration and experimentation; Sharing, collaboration, Improving, passing on information; Coaching, change and improving, passing on information; Challenging and suggesting, exploration and experimentation; Sharing, collaboration; and Trouble-shooting. Benefits of mentoring were discussed under six categories: Dialogue and new ideas; self-awareness and motivation; emotional benefits; and professional improvement; mutual benefit; emotional betterment, modelling and emulation; and sharing, experimentation, dynamism. All mentors experienced difficulties in mentoring at some part in their employment. Mentoring pairs did something to resolve mentoring difficulties when they arose. The mentee holds the key to the success of the mentoring relationship.